Changes in psychosocial and physical working conditions and psychotropic medication in ageing public sector employees: a record-linkage follow-up study. Issue 7 (12th July 2017) - Kouvonen, Anne; Mänty, Minna; Lallukka, Tea; Pietiläinen, Olli; Lahelma, Eero; Rahkonen, Ossi
Abstract : Objectives: To investigate whether changes in psychosocial and physical working conditions are associated with subsequent psychotropic medication in ageing employees. Methods: Data were from the Helsinki Health Study, a cohort study of Finnish municipal employees, aged 40–60 years at phase 1 (2000–2002). Changes in psychosocial and physical working conditions were measured between phase 1 and phase 2 (2007). Survey data were longitudinally linked to data on prescribed, reimbursed psychotropic medication purchases (Anatomical Therapeutic Chemical) obtained from the registers of the Social Insurance Institution of Finland between the phase 2 survey and December 2013 (N=3587; 80% women). Outcomes were any psychotropic medication; antidepressants (N06A); anxiolytics (N05B); and sedatives and hypnotics (N05C). Cox regression analyses were performed. Results: During the follow-up, 28% of the participants were prescribed psychotropic medication. Repeated exposures to low job control, high job demands and high physical work load were associated with an increased risk of subsequent antidepressant and anxiolytic medication. Increased and repeated exposure to high physical work load, increased job control and repeated high job demands were associated with subsequent sedative and hypnotic medication. Age and sex-adjusted HR varied from 1.18 to 1.66. Improvement in job control was associated with a lower risk of anxiolytic, but with a higher risk of sedatives and hypnotic medication. Decreased physical work load was associated with a lower risk of antidepressant and anxiolytic medications. Conclusion: Improvement in working conditions could lower the risk of mental ill-health indicated by psychotropic medication.